[tex] \frac {1}{1-z} = \sum_{n=0}^{\infty} (\frac {(z-i)^n}{(1-i)^{n+1}}[/tex](adsbygoogle = window.adsbygoogle || []).push({});

we have to prove that, its our problem. So we start and we get,

[tex] \frac {1}{1-z} = \frac {1}{(1-i)-(z-i)} = \frac {1}{1-i} (\frac {1}{1- \frac {z-i}{1-i}})[/tex]

and then i think we're supposed to go to a power series or something, but i don't know, i'm not sure how to get to there, from here. help?

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Taylor Series

**Physics Forums | Science Articles, Homework Help, Discussion**